Implementasi Algoritma Penjadwalan Multilevel Feedback Queue pada Aplikasi Berbasis Flutter - Artia, Fransiska; I Gede Maha; M. Rakhmat Dramaga; Aqwam Rosadi Kardian (Universitas Sari Mutiara Indonesia Medan, 2023)
Application development has experienced a shift towards a cross-platform approach, where developers can write code once for multiple platforms. Flutter, as a fast-growing cross-platform framework with a wide community is one of the most popular cross-platform frameworks today. However, along with that, there is an increase in application complexity which makes the concept of multitasking very important. This article proposes the implementation of the Multilevel Feedback Queue (MLQ) scheduling algorithm in Flutter applications, which can help manage tasks and improve application efficiency. This research aims to examine the changes in application efficiency after the implementation of MLQ, as well as examine whether the changes remain relevant on different operating systems, namely Windows and Android. The implemented MLQ algorithm is an algorithm with adjustments to the calculation of time quantum and integration with the Shortest Job First (SJF) algorithm based on previous research. Tests were conducted using the Flutter benchmarking feature to measure the application frame rate before and after MLQ implementation on Windows and Android. The results of this study found that the implementation of MLQ increased application efficiency by 269% on the Windows operating system and 155% on the Android operating system.